Kompleksitas Kekerasan Keagaamaan dalam Kehidupan Umat Beragama di Indonesia: Suatu Tinjauan Sosiologis - Nashir, Haedar (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2015)
Religion and religious organizations actually carrying the mission of salvation, peace, happiness, and life for the good of mankind. Hence a paradox if in fact religious life religious violence. The religious violence often occurs in the sacred and complex dimensions, both rooted in the aspect of religion and other dimensions of understanding of the dynamics of the life of this beragama.Studi tried to examine the roots and dimensions of the religious violence in the lives of the people of Indonesia to date, which often happens quite hard and complicated , By using a sociological perspective, this study tries mencandra complex relationships between the dimensions of understanding inherent in the system of belief (belief system) in every religion with economic interests and political and social plurality reality in people's lives beragama.Kajian dynamics of religious violence is sociologically be very important and relevant as the case often occurs repeatedly. At the same time the study is also important in order to obtain the understanding and solving solutions in religious violence in the country.